1988
DOI: 10.1159/000212971
|View full text |Cite
|
Sign up to set email alerts
|

Markers of the Nutritional Status in Acutely Ill Elderly Patients

Abstract: We recorded anthropometric and laboratory data in 98 sick old people on admission to a high-dependency unit. The measurement of triceps skinfold thickness and arm muscle area was feasible even in very ill people, while measurement of the body mass index was difficult and sometimes unreliable. Anthropometric measurements indicated that our study group was better nourished than a local population, with just 3 subjects (3%) being fat depleted and a further 4 (5%) being protein depleted. Serum albumin was the labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…In acutely ill elderly patients, previous authors (Finucane et al, 1988) found no correlation between transferrin and some indirect indexes of body composition as arm muscle area and triceps skinfold thickness. They concluded that plasma transferrin is not a useful marker of the nutritional status.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In acutely ill elderly patients, previous authors (Finucane et al, 1988) found no correlation between transferrin and some indirect indexes of body composition as arm muscle area and triceps skinfold thickness. They concluded that plasma transferrin is not a useful marker of the nutritional status.…”
Section: Discussionmentioning
confidence: 82%
“…Probably other factors, beside malnutrition, could influence transferrin values. It is already known that transferrin levels increases in iron deficiency anemia and decreases in hepatic cirrhosis, iron overload and acute and chronic infections (Finucane et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same reference ranges, low protein con centrations were present in 10-26%, and un satisfactory vitamin values in 10-37% of our patients. Other studies investigating protein concentrations in geriatric patients showed even higher proportions of low concentra tions or lower mean values, especially for albumin [4,5,12,14,18]. In institutionalized elderly, wide ranges of values have been re ported [46,47,52,53], Similarly, reports on vitamin values are conflicting.…”
Section: Nutritional Statusmentioning
confidence: 99%
“…erheblich einschränkt. [16][17][18]. Da seine Serumkonzentration im Alter um 0,8 g/l pro Altersdekade abnimmt, gilt Albumin als der beste Marker zur Abschätzung des "biologischen Alters" [19].…”
Section: Serumproteineunclassified